2021
DOI: 10.1007/s00436-021-07386-3
|View full text |Cite
|
Sign up to set email alerts
|

First molecular description of Macracanthorhynchus hirudinaceus in wild boars from Italy with pathomorphological and epidemiological insights

Abstract: Macracanthorhynchus hirudinaceus is a zoonotic parasite affecting suids worldwide which are the definitive hosts for this helminth species. Macracanthorhynchus hirudinaceus is of significant economic and management concern due to its pathogenicity, causing intestinal obstruction and perforation in the definitive hosts. Current study is the preliminary investigation from Sardinia, Italy, reporting the pathomorphological findings and molecular characterization of M. hirudinaceus in the wild boars (Sus scrofa mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The Sardinian studies showed the smallest differences in incidence; the difference was only −0.75% (Tables 4-6). Cameroon pig farm 0.2% 2022 [35] Italy (Sardinia) woodland area wild boar 13.6% 2022 [45] Brazil woodland area wild boar 1.04% 2023 [38] Research data on M. hirudinaceus from different parts of the world. Occurrence of A. suum and M. hirudinaceus by country, differences compared to Hungarian data.…”
Section: Discussionmentioning
confidence: 99%
“…The Sardinian studies showed the smallest differences in incidence; the difference was only −0.75% (Tables 4-6). Cameroon pig farm 0.2% 2022 [35] Italy (Sardinia) woodland area wild boar 13.6% 2022 [45] Brazil woodland area wild boar 1.04% 2023 [38] Research data on M. hirudinaceus from different parts of the world. Occurrence of A. suum and M. hirudinaceus by country, differences compared to Hungarian data.…”
Section: Discussionmentioning
confidence: 99%
“…hirudinaceus in P . siculus is unprecedented and may be explained by the high prevalence of this zoonotic helminth in wild boar and intermediate hosts from the same area [ 65 , 66 ]. Although little is known about the role of reptiles as paratenic hosts of M .…”
Section: Discussionmentioning
confidence: 99%
“…To date, human cases of accidental infection through the ingestion of intermediate/paratenic hosts parasitized by M . hirudinaceus have been described mostly from other countries (i.e., Morocco, Argentina, Iran, and Tunisia) [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the genus includes four species: M. hirudinaceus (Pallas 1781) Travassos 1917 (type species), M. catulinus Kostylew 1927, M. rinaceid Dollfus 1953 and M. ingens (von Linstow 1879) Meyer 1932 (Amin, 2013 ). Species of Macracanthorhynchus have been the target of numerous studies related to their ecology, host-parasite relationships, pathogenicity, taxonomy, and systematics (Schmidt, 1971 ; Near et al, 1998 ; Richardson, 2005 , 2014 ; García-Varela & Nadler, 2005 ; Kennedy, 2006 ; Migliore et al, 2021 ; Dessì et al, 2021 ). Macracanthorhynchus ingens was described from the intestine of a racoon ( Procyon lotor Linnaeus) from North America (see Richardson, 2014 ), and since then this acanthocephalan has been recorded in other definitive hosts such as black bear ( Ursus americanus Pallas), domestic dog ( Canis familiaris Linnaeus), coyote ( Canis latrans Say), hog-nosed skunk ( Conepatus leuconotus Lichtenstein), eastern striped skunk ( Mephitis mephitis Schreber), mink ( Neovison vison Schreber), hairy-tailed mole ( Parascalops breweri Bachman), spotted skunk ( Spilogale gracilis Merriam) and gray fox ( Urocyon cinereoargenteus Schreber) in diverse countries such as Canada, United States, Mexico, Nicaragua and Colombia (García-Varela & Nadler, 2005 ; Richardson, 2014 ; Richardson et al, 2017 ; Hartnett et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%